In situ electrochemical monitoring of signaling transduction in plants. Implications on phylogenetic aspects of defense response - Doménech-Carbó, Antonio; Dias, Daiane; Prieto-Mossi, Josefa; Montoya, Noemí (Electroanalysis, 2023)
In situ recording of the voltammetric response of leaves of several Asparagales, Caryophyllales, and Saxifragales plants at platinum and graphite microelectrodes is described. These provide information on the temporal evolution of H2O2 production and electroactive defense compounds (salicylic and jasmonic acids) associated with the stress generated by electrode insertion. Comparison of voltammetric data in the absence and presence of ROS generation revealed significant differences in the kinetics of the plant response. Reported data suggest that signaling pathway changes could be associated with the phylogenetic divergence between monocots and eudicots and the subsequent separation of the Caryophyllales from other eudicots.
Keywords: defense signaling; electrochemistry; in situ; phylogeny; ROS; Scopus; JCR